(untitled) (Superficies y Vacío, 2013)
Small hexagonal-shaped ZnO Nanorods (ZnO-NRs) were synthesized on PET (Polyethylene terephthalate)/ITO substrates through a conventional wet chemical method assisted by ultrasound using Zn(NO3)2 and hexamethylenetetramine (HMT) as precursors. The reaction was carried out in three steps: i) ZnO seeds synthesis, ii) ZnO seeds deposition, and iii) ultrasound-assisted unidirectional growth of ZnO-NRs. Aligned ZnO-NRs were characterized by HRTEM, SAED, EFSEM, UV-Vis and Raman spectroscopy; their lengths and thicknesses ranged 240 – 350 nm and 25 – 80 nm, respectively on PET/ITO substrates. Results indicated that ZnO-NRs were grown on a 200 nm thick ZnO rigid film formed by a dipcoating method which has brittle nature. It could hinder the use of these substrates in the construction of flexible devices. ZnO-NRs/(PET/ITO) transmits a UV-Vis radiation between 50% and 80%, whose variation depends on the synthesis conditions. Optical band-gap of the synthesized material approximately 3.3 eV is independent on the Nanorods’ dimensions. Experimental and structural details are also discussed in this work.